Game Popularity Tracking System - Joseph Alexander Budiarto (Institute of Research and Community Outreach - Petra Christian University, 2018)
The purpose of this research is to develop a game popularity tracking system that can generate popularity values once every 24 hours using daily data from Google Analytics. Within the scope of this project, game popularity is defined as the fact that the quality of a certain game is liked by many people. There are 5 metrics that can be used to calculate game popularity: users count, unique page views (UPV), average time on page (ATP), the difference of unique page views, and average time on page from the day before. To generate the popularity values daily, the combination of weighted average, exponential moving average, and exponential smoothing algorithm are used. The final result of this project is a service that can run automatically and also provides an HTTP API that could fetch popularity values of games from gaming sites, sending the data in XML format for other services to use when needed. The service is built using Node.JS and other in-trend technologies such as Google Analytics API v4, OAuth 2.0, Express.JS, etc.